The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0001-3765201820170842
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation of Brachiaria brizantha cv. Marandu by biolistics

Abstract: Brachiaria brizantha is a forage grass well adapted to tropical areas and cultivated in millions of hectares in Brazil. The apomictic mode of reproduction in this species, in addition to differences in ploidy between sexual and apomictic plants, impairs crossbreeding. The development of a methodology to transform apomictic cultivars will provide an option to introduce agronomic important traits to B. brizantha cv. Marandu. In addition, it will open the possibility to study in vivo the function of candidate gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These authors also observed that the apomictic genotype showed higher percentages of somatic embryogenesis and regeneration (77 and 64%, respectively) than the sexual one (45 and 21%), highlighting a genotype dependent response in U. brizantha. Afterward, with the optimal culture conditions for somatic embryogenesis described above, embryogenic calli, and cell suspensions were bombarded with plasmids containing GUS and hptII cassettes and tested for transient and stable expression (Cabral et al, 2018). The phased selection on hygromycin (5-10-20 mg/L) only delivered one transgenic plant, and it was negative for GUS histochemical assay and the amplification of the hptII gene by PCR.…”
Section: Urochloa (Syn Brachiaria) Von Ledebourmentioning
confidence: 99%
“…These authors also observed that the apomictic genotype showed higher percentages of somatic embryogenesis and regeneration (77 and 64%, respectively) than the sexual one (45 and 21%), highlighting a genotype dependent response in U. brizantha. Afterward, with the optimal culture conditions for somatic embryogenesis described above, embryogenic calli, and cell suspensions were bombarded with plasmids containing GUS and hptII cassettes and tested for transient and stable expression (Cabral et al, 2018). The phased selection on hygromycin (5-10-20 mg/L) only delivered one transgenic plant, and it was negative for GUS histochemical assay and the amplification of the hptII gene by PCR.…”
Section: Urochloa (Syn Brachiaria) Von Ledebourmentioning
confidence: 99%
“…Occasionally, a meiotic ES can be observed in apomictic plants, a feature that led to the conclusion that apomixis in Brachiaria is facultative [5]. Because apomixis leads to the production of clonal seeds, and there is a possibility of genetic control of the trait, it gained the attention of the international scientific community working with plant reproduction and breeding in different species [6][7][8][9][10][11][12]. Identification of genes related to apomixis may, in one hand, allow the transfer of apomixis to important crops, fixing superior genotypes maintaining hybrid vigor, and on the other hand, the turn off of apomixis in natural apomictic plants such as Brachiaria, simplifying breeding.…”
Section: Introductionmentioning
confidence: 99%